ANALISIS LITERASI KEUANGAN, EFIKASI KEUANGAN DAN PENGALAMAN KEUANGAN TERHADAP KEPUTUSAN INVESTASI MAHASISWA DI KOTA BATAM - Gultom, Sonia Cladia; Tobing, Vargo Christian L. (LPPM Universitas Putera Batam, 2024)
This research aims to determine and test the factors that influence financial literacy, financial efficacy, and financial experience on student investment decisions. The population in this study were accounting students at five universities in the city of Batam and the data collection method was the questionnaire method. The sample uses the Slovin formula calculation and the statements in the questionnaire use a Likert scale. The number of accounting students who were respondents in this study was 98 respondents with 26 questions. The results of hypothesis testing in this study state that partially financial literacy has a significant effect on investment decisions, financial efficacy has a significant effect on investment decisions, and financial experience has a significant effect on investment decisions. Simultaneous testing shows that financial literacy, financial efficacy and financial experience simultaneously have a significant influence on investment decisions. in the coefficient test, the Adjusted R Square value was obtained at 0.771, which means that the percentage influence of financial literacy, financial efficacy and financial experience is 77.1% and the remaining 22.9% is influenced by other variables.